On the Problem of Suicides and Suicidal Behaviour in Modern Azerbaijan - Elibegova, Anzhela; Ghazaryan, Izabella (Bulletin of Yerevan University E: Philosophy, Psychology, 2016)
According to WHO data, over 800 thousand people die every year, and a significantly higher number of people attempt suicide. The article analyses the psychology of suicidal behaviour and the reasons for its active demonstrations in Azerbaijan over the recent years. Cases of neurotic diseases, anxiety disorders and depressions have sharply grown in Azerbaijan. The number of suicides and suicide attempts by citizens of various age and social groups has also seen an increase. In addition, suicides, which get more every day in Azerbaijan, tend to give preference to the method of demonstrative self-immolation. The article analyses the social conditions and psychological problems as causes of suicide in Azerbaijan, as well as the aggressive behaviour of the society displayed in bloody murders and in increased autoaggressive behaviour.
Keywords: Azerbaijan, suicide, autoaggressive behaviour, self-immolation